Pengaruh Sistem Informasi Penerimaan Pajak Reklame terhadap Peningkatan Pendapatan Asli Daerah Kabupaten Bengkalis - Irawan Fakhrudin Mahalizikri; Nurfaizana Arnabilla (STAI Auliaurrasyidin Tembilahan, 2021)
This article aims to determine the effect of the advertisement tax revenue information system on increasing the local revenue of Bengkalis Regency. The information system applied is still using the advertisement information system manually. Where the manual information system is applied: the first is the information system for the management and calculation of the advertisement tax, the second is the information system for the appeal of the taxpayer and the organizer of the advertisement tax through electronic media and the third banner is the information system for the recapitulation of targets and realization of the advertisement tax using the standard application of Microsoft Excel. The researcher used the collection techniques: interviews, documentation, questionnaires, and literature studies. The data analysis technique used: respondent's data test, data quality test, classical assumption test, hypothesis test and simple linear regression test, while the results studied were known in the t-test (partial) that the value of tcount 8.168> ttable 1.983. Meanwhile, based on the significant value of the t-test (partial) it can be seen in the sig table column that the significant value is 0.000 <0.05. So it can be concluded that there is an influence between the Advertising Tax Revenue Information System variable (X) on the Regional Original Income Increase variable (Y) by 39.3%, the rest is influenced by other variables of 60.7%